Fenomena Penggunaan Dialek Gyeongsang-do (경상도 방언) dalam Drama Korea ‘Reply 1994 (응답하라 1994)’ - Leandro, Jose; Prasetyanti, Keren; Pniel, Amanda; Azizah, Asma; Ansas, Velayeti Nurfitriana (DBSMB, Vocational College of Universitas Gadjah Mada, 2023)
This study focuses on discussing the use of the Gyeongsang-do dialect found in the Korean drama 'Reply 1994 (응답하라 1994)'. The purpose of this study was to determine the most used dialect by the characters in the drama. This research was conducted because many foreign viewers from outside Korea find it hard to understand the use of Korean dialects due to the various types. By doing this research, hopefully, that Korean drama viewers who come from outside Korea would know and understand the use of dialect used in the drama. The method used in this research is descriptive qualitative with the use of listening and note-taking techniques. In this study, the dialects found in the Korean drama 'Reply 1994 (응답하라 1994)' were analyzed and then classified based on the grammar and vocabulary used in the Gyeongsang-do dialect. The results of this study indicate that in the Korean drama 'Reply 1994 (응답하라 1994)', from 354 speeches containing the Gyeongsang-do dialect, there are 210 speeches in the grammatical category and 246 speeches in the vocabulary category.